Protein Profile Analysis of Ericerus pela (Hemiptera: Coccoidea) Egg. Issue 1 (25th January 2018) - Hu, Yanhong; Chen, Xiaoming; Yang, Pu
Abstract: The transformation from embryo to first instar nymph is an essential process in the insect life cycle. In order to characterize protein expression in the Ericerus pela Chavannes (Hemiptera: Coccoidea) egg, high-throughput proteomics and bioinformatics methods were used. A total of 678 peptides were identified and assigned to 358 protein groups. The proteins exhibited a wide range of molecular weight (3.50–495.12 kDa) and isoelectric points (3.50–13.1). Gene Ontology annotation showed that the majority of proteins were associated with cellular processes, metabolic processes, and response to stimulus processes. The predominant molecular functions of E. pela egg proteins included binding, catalytic activity, transporter activity, and structural molecule activity. Kyoto Encyclopedia of Genes and Genomes annotations identified 137 pathways, and most proteins were assigned to metabolism events, including many enzymes participating in energy metabolism, protein folding, sorting, and degradation. The processes and functions of the identified proteins were closely related to the physiological status of egg and embryo development. We conclude that some identified proteins are related to important egg biological characteristics, and regard them as the target proteins for future study.